Creating Equity Education for First Nation, Métis and Inuit Students in Ontario Provincial Classrooms - Restoule desOrmeaux, Tammy (Scholarship@Western, 2023)
There is an education gap in the achievement of Indigenous students today linked to the colonial domination era. Due to inequities in provincial education systems, Indigenous students have not been performing and succeeding academically like non-Indigenous students. Since 2015, strategies and solutions have emerged to correct this ongoing Canadian issue. 94 Calls to Action by the Truth and Reconciliation Commission of Canada (TRC) were posted to help repair the harm caused by residential schools and move forward with reconciliation. This Organizational Plan (OIP) will focus on École secondaire catholique Entourage (ESCEntourage) (a pseudonym) to improve instruction for Indigenous students' academic, social, and emotional achievement. This plan aims to help FNMI students succeed academically like their dominant counterparts, graduate, and be able to move on to post-secondary studies to contribute fully to society as active citizens. This OIP offers teaching practices aimed at helping instruction become more culturally relevant and inclusive and to create challenges for students as part of equity-driven work. Given its roots in assisting underprivileged and oppressed communities towards more equitable solutions, a critical social justice lens is used as the underpinning framework. I draw on transformational and culturally relevant leadership (CRL) approaches to persuade and inspire early adopter teachers to recognize and grasp the significance of integrating Indigenous viewpoints and adopting cultural practices in their classrooms.